Complex Odontoma: A Case Report with Micro-Computed Tomography Findings - L. A. N. Santos; L. J. Lopes; G. D. Roque-Torres; V. F. Oliveira; D. Q. Freitas (Hindawi Limited, 2016)
Odontomas are the most common benign tumors of odontogenic origin. They are normally diagnosed on routine radiographs, due to the absence of symptoms. Histopathologic evaluation confirms the diagnosis especially in cases of complex odontoma, which may be confused during radiographic examination with an osteoma or other highly calcified bone lesions. The micro-CT is a new technology that enables three-dimensional analysis with better spatial resolution compared with cone beam computed tomography. Another great advantage of this technology is that the sample does not need special preparation or destruction in the sectioned area as in histopathologic evaluation. An odontoma with CBCT and microtomography images is presented in a 26-year-old man. It was first observed on panoramic radiographs and then by CBCT. The lesion and the impacted third molar were surgically excised using a modified Neumann approach. After removal, it was evaluated by histopathology and microtomography to confirm the diagnostic hypothesis. According to the results, micro-CT enabled the assessment of the sample similar to histopathology, without destruction of the sample. With further development, micro-CT could be a powerful diagnostic tool in future research.